Problema protocronismului. Precizări - Edgar Papu (Revista de Istorie și Teorie Literară)
We are dealing with the ultimate variant of the Romanian Protochronism theory, conceived by the scholar Edgar Papu (1908-1993), reproduced serially in the newspaper “Românul” between March and July 1991. His idea about the Romanian aesthetic forms anticipating or preparing currents, motives or procedures that were later to be experienced and dealt with by the Western culture was published twice before (1977 and 1989), but this one is the first uncensored text diffused after the fall of the communist regime in Romania. Running chronologically, the paper starts with a 16th c. work – contemporary to Machiavelli’s The Prince (1513) – due to the Lord of Walachia, Néagoé Bassarab, entitled The Lectures meant for his son Theodosius (1519-1521), which establishes a canon of reigning principles and skills at hand to his heir to the throne, considered by the author Edgar Papu to anticipate the appearance of the Baroque type of “hombre secreto” described in the treaties of the Jesuit monk Baltasar Gracián, called El Discreto (1646) and Oráculo manual y arte de prudencia (1647). At the beginning of the 18th c., he discovers that the writings of the noble scholar Demeter Cantemïr (prince of Moldavia), entitled Hieroglyphic History (1705, published in 1883), foreshadows the Byronian type of Romanticism (illustrated by many masterpieces as Alfred de Vigny’s Moses, Mihaïl Lermontov’s The Demon, Eugene Onegin by Aleksandr Pushkin, Mihaï Eminescu’s poem The Morning Star or Thus Spoke Zarathustra by Friedrich Nietzsche). The History of the Ottoman Empire (1714-1716) by the same Demeter Cantemïr influenced Montesquieu’s historiographical method in conceiving his book, called Considerations on the Causes of the Greatness of the Romans and their Decline (1734). As we near to the present day, the author Edgar Papu highlights more than 50 autochthonous works that possess different anticipating virtues, finding an increased frequency of Romanian writers capable of protruding their own principles and aesthetic solutions in other literary fields (Ion Heliade[1]Rădulescu, Mihai Eminescu, Ion Creangă, Al. Macedonski, George Bacovia, Mateiu Caragiale, Liviu Rebreanu, Marin Sorescu, Nichita Stănescu). This theory scored a new axiological attitude towards the Romanian literature, remaining a possible guide-line in re-assessing the history of ideas.